-5(z+7)=-6z

Simple and best practice solution for -5(z+7)=-6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(z+7)=-6z equation:


-5(z+7)=-6z

We simplify the equation to the form, which is simple to understand
-5(z+7)=-6z

Reorder the terms in parentheses
+(-5z-35)=-6z

Remove unnecessary parentheses
-5z-35=-6z

We move all terms containing z to the left and all other terms to the right.
-5z+6z=+35

We simplify left and right side of the equation.
+1z=+35

We divide both sides of the equation by 1 to get z.
z=35

See similar equations:

| x*2-x=12 | | 5n-4(n-6)=2+2n | | 10-(3y-3)=2-4y | | x/8-1=-5 | | 2x*2-x=45 | | 3xy^2-2xy+2=-3y^2+y+4x | | 10-4(x-5)=11-x | | 4v^2-4v=15v | | h=4f | | x^2-20x=-53 | | -4x-9+3(2x+5)-2= | | (-7x+2)-(-6x-5)=3 | | 12(t-2)+6t=6(3t+3)-12 | | 3b=11b | | 7[3-(8x-3)]+4x=0 | | 3x^2+10x-32=0 | | x^2=-14x-24 | | (4k+5)(k+7)=0 | | 12x-6+2x-3=11x-3+2x | | n^2+60=-16n | | 5(4x+8)=-40+20 | | -5(x-7)-5=30 | | 5(2x+5)=-29+44 | | 4y^2-2=7y | | (3x+6)(9x+6)=0 | | (2x+3)(5y-9)= | | 6x^2+8=8x^2-8 | | 2(6x+24)=2(7x+14) | | x*2+9x+20=0 | | 8x^2+531=-2x^2+571 | | -3v-(3-6v)=-10+4v | | 2y-54=12 |

Equations solver categories